Implementation of a Web-Based Health Service Information System to Support Homecare Services in DKI Jakarta - Akbar, Sandi; Ismaningsih, Ismaningsih; Muawanah, Siti (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The implementation of a web-based health service information system plays a vital role in supporting homecare services in DKI Jakarta by enhancing communication, accessibility, and service efficiency. This study employs a qualitative research method through literature review and library research to explore the design, development, and impact of such systems in the context of homecare. The analysis synthesizes findings from various studies on web-based platforms that facilitate interaction between patients, healthcare providers, and administrative staff, emphasizing functional accessibility, user engagement, and technology integration. Key aspects include the system’s ability to provide real-time updates on homecare visits, enable secure messaging, and streamline scheduling and service delivery. The research highlights that ease of access and relevance of information to user needs are critical factors influencing system adoption and effectiveness. Furthermore, the study discusses the benefits observed for multiple stakeholders: patients experience improved access to healthcare information and services; healthcare providers benefit from better coordination and resource management; and administrators gain enhanced oversight and business growth opportunities. Challenges such as digital literacy, infrastructure limitations, and privacy concerns are also addressed. The findings suggest that a well-designed web-based health information system, supported by complementary applications and platforms, can significantly improve the quality and reach of homecare services. This study contributes to the understanding of digital health interventions in urban Indonesian settings and offers practical recommendations for policymakers and healthcare organizations aiming to implement or enhance web-based homecare systems.